Neoadjuvant durvalumab improves survival in early triple-negative breast cancer independent of pathological complete response - Loibl, Sibylle; Schneeweiss, Andreas; Huober, J.; Braun, M.; Rey, J.; Blohmer, J. -U.; Furlanetto, J.; Zahm, D. -M.; Hanusch, C.; Thomalla, J.; Jackisch, C.; Staib, P.; et al. (Annals of oncology, 2022)
Background - Addition of immune checkpoint inhibitors to neoadjuvant chemotherapy (NACT) is a promising strategy in early breast cancer, but the optimal duration of therapy is currently unknown. In the GeparNuevo (NCT02685059) trial, addition of durvalumab to NACT as previously reported led to a moderate increase in pathological complete response (pCR) rate by an absolute 9% (P = 0.287). - Patients and methods - Patients with cT1b-cT4a-d triple-negative breast cancer (TNBC) received durvalumab 1.5 g or placebo every 4 weeks added to nab-paclitaxel 125 mg/m2 weekly for 12 weeks, followed by durvalumab/placebo every 4 weeks plus epirubicin/cyclophosphamide every 2 weeks followed by surgery. Durvalumab was not continued after surgery. The primary objective was pCR. Secondary endpoints included invasive disease-free survival (iDFS), distant disease-free survival (DDFS) and overall survival (OS). - Results - A total of 174 patients were randomised between June 2016 and October 2017. After a median follow-up of 43.7 months, 34 events had occurred. Despite a non-significant increase in the pCR rate, significant differences were observed for 3-year iDFS, DDFS and OS: iDFS was 85.6% with durvalumab versus 77.2% with placebo [hazard ratio (HR) 0.48, 95% confidence interval (CI) 0.24-0.97, stratified log-rank P = 0.036]; DDFS 91.7% versus 78.4% (HR 0.31, 95% CI 0.13-0.74, P = 0.005); OS 95.2% versus 83.5% (HR 0.24, 95% CI 0.08-0.72, P = 0.006). pCR patients had 3-year iDFS of 95.5% with durvalumab and 86.1% without (HR 0.22, 95% CI 0.05-1.06). In the non-pCR cohort 3-year iDFS was 76.3% versus 69.7% (HR 0.67, 95% CI 0.29-1.54). Multivariable analysis confirmed a durvalumab effect independent of the pCR effect. No new safety signals occurred. - Conclusions - Durvalumab added to NACT in TNBC significantly improved survival despite a modest pCR increase and no adjuvant component of durvalumab. Additional studies are needed to clarify the optimal duration and sequence of checkpoint inhibitors in the treatment of early TNBC.